2013
DOI: 10.2131/jts.38.379
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid attenuates hepatic accumulation of cholesterol esters but aggravates liver injury and inflammation in mice fed a cholate-supplemented high-fat diet

Abstract: -The administration of a sodium cholate-supplemented high-fat (CAHF) diet in mice induced the predominant accumulation of cholesterol esters (CE) in the liver and biochemical and histological features of liver injury. Cholesteryl oleate was the most abundant CE found in the liver of the mice fed the CAHF diet. We examined the effect of ethyl eicosapentaenoate (EPA) on hepatic CE accumulation and liver injury in the mice fed the CAHF diet. The EPA supplementation suppressed the elevation in the level of cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The reasons for this are unknown, although hypothetically, the greater range of dietary intakes for DHA compared to EPA may have made associations for DHA easier to detect. However, importantly some studies have reported that EPA is less effective than DHA in suppressing inflammation and may actually be pro‐inflammatory . This may result from EPA being metabolised to leukotriene B 5 , which has weak pro‐inflammatory activity and prostaglandin E 3 , which disrupts the intestinal epithelial barrier .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this are unknown, although hypothetically, the greater range of dietary intakes for DHA compared to EPA may have made associations for DHA easier to detect. However, importantly some studies have reported that EPA is less effective than DHA in suppressing inflammation and may actually be pro‐inflammatory . This may result from EPA being metabolised to leukotriene B 5 , which has weak pro‐inflammatory activity and prostaglandin E 3 , which disrupts the intestinal epithelial barrier .…”
Section: Discussionmentioning
confidence: 99%
“…However, importantly some studies have reported that EPA is less effective than DHA in suppressing inflammation 26 and may actually be pro-inflammatory. 27 This may result from EPA being metabolised to leukotriene B 5 , which has weak pro-inflammatory activity 7 and prostaglandin E 3 , which disrupts the intestinal epithelial barrier. 28 Moreover, while one would assume that if DHA and EPA were present in identical food sources (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for the biochemical and histological assessment of liver injury induced by bile acid have previously been reported .…”
Section: Methodsmentioning
confidence: 99%
“…Total lipids were extracted from the liver as reported by Bligh and Dyer . Cholesteryl esters (CE), TG, and total phospholipids (PL) were purified on silica gel thin‐layer chromatography (TLC) and their fatty acid content determined using gas–liquid chromatography as described previously . Heptadecanoic acid (17:0) was added to the lipid fractions as an internal standard for the quantification of fatty acid content.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Watanabe et al . reported that EPA supplementation reduced hepatic cholesterol ester accumulation but aggravated liver injury and associated inflammatory responses in a mouse model of sodium cholate-supplemented high-fat diet-induced steatohepatitis [ 33 ]. In the present study, we investigated and compared the effects of the major n-3 PUFAs, EPA and DHA, on attenuation of atherogenic high-fat (AHF) diet-induced NAFLD.…”
Section: Introductionmentioning
confidence: 99%